Soil physico-chemical properties in jhum fields and forests of Sagalee and Namsai region in Arunachal Pradesh - Arunachalam, Ayyanadar (Indian Journal of Agroforestry, 2022)
A study was conducted to compare the soil properties of shifting agricultural systems in two geographically isolated zones in the state Arunachal Pradesh. The soils were sandy loam and loamy sand in nature. Water holding capacity (WHC) of the topsoil layer was always greater as compared to the lower depth in all the sites. Soil pH did not show much seasonal variation, except during the rainy season (April and October), where the value was low in the subsurface (15-30 cm) layer. Soil organic C (SOC) decreased with increasing soil depth. As expected, it was highest in the forest as compared to the jhum cultivation fields in both eastern and western Arunachal Himalaya. Site-wise variations in soil organic carbon (SOC) was significant (P<0.001). The concentration of nitrate-N was greater than ammonium-N throughout the study and total Kjeldahl N (TKN) decreased with increasing soil depth. TKN was also highest in the forest stands as compared to the jhum systems. In all eight sites studied, the concentration of TKN in soil was highest during April (spring) and minimum during June and August (rainy season) and it showed a declining trend with soil depth in all stands. Ammonium N decreased with increasing soil depth in all the sites. The concentration of ammonium-N was greater in the forest soils. Nitrate-N concentration (NO3-N) also decreased with increasing soil depth in both zones. A significantly rapid decrease in NO3-N was observed in the jhum fields of the eastern Arunachal sites. Available P was highest in the eastern Arunachal sites as compared to the western ones. With increasing soil depth, available P also showed a decreasing trend in both sites; the rate of decrease was however faster in the eastern Arunachal sites. In all eight sites, the concentration of available-P in the soil was highest either during the rainy and/or autumn season and minimum during the winter season and it showed a declining trend with soil depth in all stands. The carbon to nitrogen ratio (C:N) was higher in the eastern Arunachal sites as compared to that in the western Arunachal sites.